Preliminary analysis of catenoid chimney cooling towers - Wiśniowski, Maciej; Walentyński, Robert; Cornik, Dawid (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
Optimization plays an important role in scientific and engineering research. This paper presents the effects of using the catenoidal shape to design the structure of a chimney cooling tower. The paper compares some geometrical variations of the catenoid with the reference existing hyperboloidal structure. It also compares internal forces, deformation and stability of the catenoidal structure. The comparison shows some predominance of the catenoid over the popular hyperboloid structure of the shell. The paper attempts to find an optimal shape of the cooling tower in order to reduce the amount of material and labor. The paper utilizes engineering tools and the designing process for chimney cooling towers.